Sleep Disorders in Pregnancy - Bazalakova, Mihaela (Seminars in Neurology, 2017)
Sleep and pregnancy are dynamic processes with unique and evolving physiological substrates. Given the “restorative hypothesis” of sleep as an anabolic process essential for cellular and tissue regeneration, the largely unexplored role of sleep in gestational physiology and pregnancy outcomes promises to be a fascinating topic. Emerging literature suggests that objectively measured or self-reported short sleep duration may be a risk for adverse pregnancy outcomes, including gestational diabetes mellitus (GDM), gestational hypertension, and cesarean delivery. In this review, we discuss obstructive sleep apnea (OSA) and restless legs syndrome (RLS), two sleep disorders prevalent in pregnancy. OSA is especially likely in high-risk pregnancy where it is associated with comorbid cardiovascular and metabolic disturbances. We review new data strongly suggesting that OSA is an independent risk factor for GDM and gestational hypertension. It remains to be seen if sleep disruption, whether or not in the context of gestational RLS and gestational OSA, is a modifiable factor for adverse pregnancy outcomes. Clinicians are encouraged to query sleep symptoms in pregnant women and to have a low threshold to pursue investigations for OSA, including the subjective symptoms of snoring, witnessed apneas, and daytime sleepiness, and also medical comorbidities, such as chronic hypertension.
Keywords: sleep; pregnancy; gestational; apnea; restless legs syndrome; outcomes